This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
excellent explanation
Questions dealing with Infinity are just too exciting...................
excellent ....................
* absolutely Brilliant *
Yes, I got the answer the same way. X = 0.2 Ans K.K.GARG,India
Beautiful.
You put the plus sign twice there between 1/6^3and1/6^4
I just divided x by 6 otherwise the answer was the same!!!
This is a simple GP question and the formula to find sum of infinite terms is =A/(1-R) where A is the first term and R is the ratio of first and second terms basically second term / first term.
L e t S = 6 1 + 6 2 1 + 6 3 1 + 6 4 1 + . . . . . . . . . . . . . . . . . . . . . ∞ M u l t i p l y i n g B o t h s i d e s b y " 6 " , w e h a v e 6 S = 1 + 6 1 + 6 2 1 + 6 3 1 + 6 4 1 + . . . . . . . . . . . . . . . . . . . . . ∞ = > 6 S = 1 + S = > 6 S − S = 1 = > 5 S = 1 o r S = 5 1 T H u s t h e a n s w e r i s S = 0 . 2
Brilliantly Explained...
Let 6 1 + 6 2 1 . . . = x . Then factor out the 6 1 from the second term onwards. Thus you end up with 6 1 + 6 1 ( 6 1 + 6 2 1 + . . . ) = x . Remember that you set the expression in the brackets as x. Thus you substitute x in for the expression in the brackets. You will end up with 6 1 + 6 1 x = x . Solve for x and you will get 0.2.
By using sum of Geometric series formula S= a(1- r^n/1-r) where a= 1/6 , common ratio r= 1/6 and n= 4 the answer is 0.2
S=a/1-r
a=1/6 & r=1/6
so
S=1/5=0.2
Equation for infinite GP , S=a/(1-r). So, S=(1/6)/(1-(1/6))=0.2
Geometric series with a1 = 1/6 and r = 1/6
Sum = a1/(1-r)
= (1/6)/(1-1/6) = (1/6)/ (5/6) = 1/5 = .2
S = a/1 - r
so a =1/6 , b = 1/36 and r = b/a =1/36 /1/6 = we get r = 1/6 so , put the value of a , r in above formula S = 1/6 /1- 1/6 = 1/5 = 0 .2
infinite sum = a / 1- r, where a is first term and r is common ratio.
here a = 1/6 = r
infinite sum = (1 /6 ) / (1 - (1 / 6) ) = 1/ 5 = 0.2
lets add 1and subtract 1 then, 1+1/6+1/6square+.....-1 now using infinite gp 1/(1-1/6) -1 6/5-1 1/5 0.2
I used the Euler's form to solve this eqn.
Problem Loading...
Note Loading...
Set Loading...
Restating the equation required,
x = 6 1 + 6 2 1 + 6 3 1 + + 6 4 1 + . . .
Multiplying both sides by 6 we obtain,
6 x = 1 + 6 1 + 6 2 1 + 6 3 1 + 6 4 1 + . . .
Notice that the RHS is equivalent to 1 + x , which can be written as
6 x = 1 + x
Solving for x , x = 5 1 = 0 . 2